Stroke as the initial manifestation of Takayasu’s arteritis: a Case report - Kumar Gupta, Anil; Chaturvedi, Deepak; Mehrotra, Yogesh; Trivedi, Hari Har (International Journal of Medical Research and Review, 2014)
Takayasu’s arteritis is a chronic inflammatory and stenotic disease of medium and large sized arteries. We report clinical, laboratory and imaging findings of a 23 year old girl who presented with history of sudden onset of left hemiparesis.,absent bilateral upper limb and right carotid pulsations, an elevated ESR of 58 mm at 1 hour. C-reactive protein level of 34.9 mg/L.Imaging studies showed non hemmorhagic acute infarct in territory of right MCA, concentric wall thickening and resultant stenosis of most of the branches of aortic arch. The diagnosis of Takayasu’s arteritis was made and was put on steroids and anticoagulants. Patient showed a good clinical response.